In-medium nucleon-nucleon elastic cross-sections determined from the nucleon induced reaction cross-section data *Supported by Natural Science Foundation of Guangxi Province (2016GXNSFFA380001, 2017GXNSFGA198001), Foundation of Guangxi Innovative Team and Distinguished Scholar in Institutions of Higher Education, and National Natural Science Foundation of China (11365004, U1867212). (April 2019) - Ou 欧, Li 立; He 何, Xue-ying 雪英
Abstract: Within the framework of the improved quantum molecular dynamics model, the medium modifications of the free nucleon-nucleon elastic cross-sections are investigated. By using various in-medium nucleon-nucleon elastic cross-sections in the model, the nucleon induced reactions on various targets are simulated, and the excitation functions of reaction cross-sections in the energy range from 25 MeV to 1 GeV are calculated. By comparing the calculations with the experimental data, the isospin, density, and momentum dependence of the medium correction factors of free nucleon-nucleon elastic cross-sections are determined.